2012 38th IEEE Photovoltaic Specialists Conference 2012
DOI: 10.1109/pvsc.2012.6318178
|View full text |Cite
|
Sign up to set email alerts
|

Non-solar photovoltaics for small space missions

Abstract: NASA has missions planned to targets in the solar system ranging from the permanently shadowed craters of Mercury to the icy reaches of the Kuiper belt and beyond. In 2011, the NASA Office of the Chief Technologist (OCT) requested the NASA Ames and Glenn Research Centers to assess the potential of small power supplies based on direct conversion of energy from radioisotope sources for future NASA missions; and in particular to assess whether alphavoltaic and betavoltaic power sources could be of potential benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The nuclear battery is widely used in severe environments such as outer space and deep sea, because of its small size, light weight, long service life, and stable output power 1‐4 . At present, miniaturized nuclear batteries mainly consist of decay particle conversion mechanism; however, radiovoltaic nuclear battery with direct conversion mode causes severe displacement damage of the semiconductor unit and shortens its service life 5‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear battery is widely used in severe environments such as outer space and deep sea, because of its small size, light weight, long service life, and stable output power 1‐4 . At present, miniaturized nuclear batteries mainly consist of decay particle conversion mechanism; however, radiovoltaic nuclear battery with direct conversion mode causes severe displacement damage of the semiconductor unit and shortens its service life 5‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…The main difference between the 2 types of batteries is that the former adds an intermediate energy conversion process, while the integrated battery structure adds a phosphor layer. So the whole energy conversion process of radioluminescent nuclear battery is from nuclear energy to light energy, and then again to electric energy . It works because phosphor layers can emit visible light under radioactive particles excitation, and the light is powerful enough to knock electrons free from atoms.…”
Section: Introductionmentioning
confidence: 99%
“…So the whole energy conversion process of radioluminescent nuclear battery is from nuclear energy to light energy, and then again to electric energy. [4][5][6] It works because phosphor layers can emit visible light under radioactive particles excitation, and the light is powerful enough to knock electrons free from atoms. The electrons go on to form a useful direct current by photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the activity and choosing a radioactive source of high‐energy are the most direct ways to improve the output performance of nuclear cells to meet the power requirements of MEMS. Previous studies have shown that the particles (α, β, γ, and X‐ray) decayed from the radioactive source can easily make radiation damage on the semiconductor for the radiovoltaic nuclear battery with direct energy conversion …”
Section: Introductionmentioning
confidence: 99%